ECONOMIC STUDIES AND LIFE CYCLE ANALYSIS OF ENERGY SELF SUFFICIENT WOOD PELLET PRODUCTION WITH THE APPLICATION OF GASIFICATION TECHNOLOGY - Abdul Rahman, Fadil
One of the strategy to reduce the amount of waste that enters landfills is to produce wood pellets from the wood waste itself. However, the energy demand in wood pellet production is very high, so a breakthrough is needed so that this energy demand can be met independently. By integrating gasification technology in the wood pellet production process, energy demand can be met by using the excess production of the wood pellets itself. Hence, that it is important to study the effect of gasification technology in fulfilling the energy demand during wood pellet production. The methods and approaches used are started by conducting a literature study to determine the appropriate technology in the wood pellet production process and converting it to energy. At 100% performance design capacity, The plant able to process wood waste into pellets of 9 tons/week. The power source scenarios in the economic study and life cycle analysis (LCA) are scenario A (PLN), scenario B (PLTD), and scenario C (PLTD-Gasification). Based on the results of an economic study using a scenario of 100% performance of design capacity, the production process using PLN as power sources, PLTD, and PLTD-Gasification are feasible to carry out with CCR values of 3.9 (PLN), 3.4 (PLTD) and 2.5 (PLTD-Gasification). Pay back period in scenario A is 4.8 years, scenario B is 5.1 years, and scenario C is 5.6 years. Based on the LCA, the emissions produced for transportation of wood waste to the plant are 1.6 kg CO2/tonne of wood and transportation emissions to the landfill are 3.2 kg CO2/tonne of wood. The pellet production process with the actual design capacity results in a greater total CO2 emission when compared to the performance of 100%, and 50% design capacity. Total CO2 emissions in the actual design capacity process are 533 kg CO2 eq/tonne of wood for scenario A, 298.3 kg CO2 eq/tonne of wood for scenario B, and 107.8 kg CO2 eq/tonne of wood for scenario C. So it can be concluded that the application of the gasification technolgy in processing wood waste into pellets is superior in terms of CO2 emissions released when compared to the use of other energy sources.